PRIMITIVE ORNAMENT: A WAY O F AN ORNAMENT OR SYMBOLIC O F ANCIENT MAGIC? - L.F. Ejvas (Academy of Cognitive and Natural Sciences, 2007)
The article is devoted to the origin, functions and symbolism of primitive images of decorative patterns. The special attention is spared to the constituents of decorative patterns of east slavs.